SYNTHESIS OF STARCH-G-POLY(OLEIC ACID) AND STARCH-G-POLY(2-DODECENYL SUCCINIC ANHYDRIDE) FOR BIOPLASTIC APPLICATIONS - Devita Purnama, Natalia
Conventional plastics made from petroleum are difficult to decompose naturally, causing environmental problems. One solution is the use of bioplastics, which are plastics made from renewable sources, environmentally friendly, and easily degraded naturally. Starch is one of the polymers that has the potential as a bioplastic material, but it has drawbacks, such as plasticity and low mechanical properties. To improve its characteristic, starch’s structure needs to be modified and one of them is through the graft copolymerization method with oleic acid and (2-Dodecen-1-yl)succinic anhydride (DDSA) monomer using cerium(IV) ammonium nitrate (CAN) as the initiator. The resulting products are starch-g-poly(oleic acid) and starch-g-poly(DDSA). The percentage of grafting (%G) and the percentage of grafting efficiency (%E) are the parameters of the graft copolymerization reaction. The optimum grafting results for starch-g-poly(oleic acid) obtained the %G value of 48% and %E of 1.8%. These results were obtained for a starch concentration of 2%, degree of polymerization (DPn) 103, starch:CAN ratio of 2:1 (w/w), and a temperature of 80 C. The optimum grafting results for starch-g-poly(DDSA) obtained the value of %G by 42% and %E by 86%. These results were obtained through a reaction using a microwave with DPn 5, starch:CAN ratio of 3:1 (w/w), 200 W power, 20 minutes initiation time, and 25 minutes polymerization time. The microwave synthesis method can be applied for further graft copolymer production because it is more effective than conventional methods. From the Fourier-Transform Infrared Spectroscopy characterization, a new peak was observed in the starch-g-poly(oleic acid) product at 2941 cm-1 due to stretching vibrations of C?H methyl and methylene and 1678 cm-1 from the C=O group from oleic acid. In starch-g-poly(DDSA) products, new peaks are seen which are typical at 2847?2914 cm-1 and 1313?1421 cm-1 from the C?H methyl and methylene groups, and 1686 cm-1 from the C=O groups. from DDSA. By X-ray diffraction characterization, broad peaks were obtained at 2? about 19° for starch-g-poly(oleic acid) and at 2? about 19.8° and 27.9° for starch-g-poly(DDSA) with lower intensity and width indicating that the product exhibits a more amorphous structure. The graft copolymer was further plasticized with the addition of PVA and glycerol as plasticizer to form a clear yellowish film. With the same composition and treatment during plasticization, the graft copolymer film still had tensile strength under the starch without modification film, but the strain value was much better. The highest elongation of starch-g-poly(oleic acid) film is 162.5% with %G 48% and starch-g-poly(DDSA) is 216.5% with %G 42%. Meanwhile, the tensile strength is 2.76 MPa and 3.91 MPa respectively.